Prime Bank Ltd: the role of small and medium enterprise (SME) banking in supporting economic growth - Karim, Mahir Shahriar (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.